Active methodological approaches in the teaching and learning of theatre and performing arts - Dos Santos Cunha, Maria José (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
Based on teaching innovation and the contemporary pedagogical trend, this article puts forth active teaching and learning methodologies that teachers committed to improving and innovating higher education can use, as traditional teaching instruments are limited, serving only as vehicles for conveying knowledge. The objectives of the work have to do with making known active teaching and learning methodologies, as they are centred on the student, which encourage their participation and whose use results in the promotion of skills of autonomy, motivation in approaching knowledge and incorporation of the contents.